Hydrogeochemical assessment of streamwater quality for its suitability for irrigation: the case of Manthong village, Kanglung (Bhutan) - Tshewang Dendup; Pema Lekzin; Tshewang Lhendup; Sonam Tobgay (Water Supply, 2022)
Mountain streams/springs are the primary irrigation water resource in Bhutan Himalaya, besides supporting drinking and other domestic needs. Successful crop production implies an adequate supply of high-quality irrigation water, among other factors. Thus, this study was conducted to assess the suitability of spring-fed streamwater for irrigation use and evaluate hydrogeochemical processes that regulate streamwater chemistry at the Manthong village in Kanglung, Bhutan. The water samples were analyzed for temperature, pH, electrical conductivity (EC), turbidity, total dissolved solute (TDS) and major ions. Piper and Durov diagrams indicated that most samples are of the intermediate type and simple dissolution or linear mixing is the primary hydrochemical process regulating streamwater chemistry. All the measured physicochemical parameters were within the acceptable thresholds of the FAO guidelines recommended for agricultural use. Analytical results of the streamwater water quality indices, including EC, %Na, residual sodium bicarbonate (RSBC), sodium adsorption ratio (SAR), Kelley's ratio (KR) and permeability index (PI), revealed its suitability for irrigation use except for magnesium hazard (MH). The Irrigation Water Quality Index (IWQI) results confirmed that the WS-1 has no restriction as irrigation water; however, WS-2 falls under the high-restriction category. The findings of this study will serve as the baseline data and guide irrigation water management and sustainable irrigation development in the region. HIGHLIGHTS A simple dissolution or linear mixing is the primary hydrochemical process regulating the streamwater chemistry resulting in mixed water type used for irrigation in Manthong village.; The spring-fed streamwater in the study area is generally fit for irrigational use as per the various irrigation water quality indices except magnesium hazard.; The IWQI provides easy and usable water quality information.;